Filarial abscess in the submandibular region - Kaur, Rupinder (Medknow Publications & Media Pvt Ltd, 2013)
Filariasis is a parasitic infectious disease caused by filarial nematode worms. These worms mainly dwell in subcutaneous tissues and lymphatics of the human host, with a predilection for lower limbs, retroperitoneal tissues, spermatic cord, and epididymis. Oral or perioral involvement of the filarial nematode is rare. This case report describes a filarial abscess in the right submandibular region. Fine needle aspiration cytology of the abscess revealed the presence of microfilaria of Wuchereria bancrofti species. The parasite was also present in the peripheral blood smear. Filarial infection presenting in this region is unusual and can cause diagnostic dilemma. The clinician can consider filariasis as one of the differential diagnosis while treating those abscesses in the orofacial region that are unresponsive to routine management, especially, patients hailing from endemic areas.